Mini review of research requirements for radioactive waste management including disposal - Grambow, Bernd (Frontiers in Nuclear Engineering, 2022)
This brief overview of research needs related to radioactive waste management and disposal is intended to provide a framework for addressing some important research questions related to historical developments and some large industrial mega-projects for geological disposal of radioactive waste that are currently being developed. Considering that the level of industrial development varies considerably between countries, research in this field of knowledge has a strong international and long-term orientation, encompassing both basic and applied research, including optimisation.